Risk Factors for Hearing Loss in the Railway Transportation Sector: Literature Review - Muhammad Rinaldo; Robiana Modjo (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Hearing loss, a significant global health problem, can significantly impact quality of life. The railway sector, with its high noise levels, is particularly vulnerable. To address this, it is crucial to focus on mitigating risk factors through noise control, PPE promotion, and regular hearing assessments. Objective: The study aims to identify factors related to hearing loss in railway sectors. By understanding these factors, the research seeks to contribute to improved workplace safety and hearing conservation programs. Method: This study employed a literature review methodology, utilizing sources from Scopus and Google Scholar. Articles were searched using the keywords